Faktor-Faktor yang Mempengaruhi Kualitas Audit: Peran Etika Profesi, Kompetensi Auditor, dan Professional Skepticism pada KAP Jawa Barat - Rinaldi, Salma Kharisa; Koenta Adji Koerniawan (LP2M IBK Nitro, 2025)
The aim of this research is to determine the influence of professional ethics, auditor competence, and professional skepticism on audit quality at Public Accounting Firms (KAP) in West Java. The data that will be used in this research is by distributing questionnaires to Public Accounting Firms in West Java. The research method used is a quantitative method. The type of research used is descriptive verification. The population used was 145 AP in 84 Public Accounting Firms in West Java and listed in the IAPI directory in 2023. The sample size was determined using the Taro Yamane formula, resulting in 62 partners as respondents. In this study, a non-probability sampling technique with a purposive sampling type was used. The data analysis technique uses descriptive, Structural Equation Modeling - Partial Least Square (PLS-SEM) analysis using SmartPLS 4.0 software, and hypothesis tests. The research results are based on the answers of respondents who are auditors at Public Accounting Firms in West Java, on average they agree that professional ethics, auditor competence and professional skepticism influence audit quality. The results of the analysis test show that (1) professional ethics has no effect on audit quality, it can be seen from the T-statistic value <1.96 and p-value >0.05, so H1 is rejected, (2) auditor competence has no effect on audit quality, It can be seen from the T-statistic value <1.96 and p-value >0.05 that H2 is rejected. (3) professional skepticism has a significant positive effect on audit quality, which can be seen from the T-statistic value >1.96 and p-value <0.05, so H3 is accepted. (4) Simultaneously professional ethics, auditor competence, and professional skepticism influence audit quality.